ANALISIS PERBANDINGAN RASIO PROFITABILITAS SEBELUM DAN SESUDAH DIKELUARKANNYA PERATURAN MENTERI KEUANGAN NOMOR 15/PMK.010/2017 DAN NOMOR 16/PMK.010/2017 TENTANG DANA SANTUNAN PADA PT JASA RAHARJA (PERSERO) PERIODE 2016-2018 - Rehan, Viola Marlita; Sasana, Hadi Sasana; Panggiarti, Endang Kartini (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2020)
This research was conducted to analyse the profitability of PT. Jasa Raharja (Persero) before and after the issuance of Minister of Finance Regulation Number 15 / PMK.010 / 2017 and Number 16 / PMK.010 / 2017 concerning compensation funds during 2016-2018. The method of analysis used in this research is qualitative descriptive study. The data used in this study are the financial statements of PT. Jasa Raharja (Persero) taken through www.jasaraharja.co.id. The results show that there has been a significant decrease in profitability when measured by Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) between before and after the implementation of Regulation of the Minister of Finance Number 15 / PMK.010 / 2017 and Number 16 / PMK.010 / 2017. This can occur due to an increase in the amount of claim compensation by 100% and changes in the receipt of flat rate fines to progressive rate fines. In the future, it is hoped that PT. Jasa Raharja (Persero) can further maximize the company's operating activities by reducing expenses or operating costs as efficiently as possible and optimizing existing resources, such as asset management and the use of capital to obtain maximum profit, so that the NPM, ROA, and ROE obtained by the company can increased. The contribution of the research is gives the knowledge that changes the regulation gives an impact to the profitability of PT Jasa Raharja (Persero).